22 Wake me up before you go go (to the cath lab): a retrospective review of activation rates of the STEMI PPCI service in galway. (16th October 2019) - Quinn, S; Elhadi, M; Frawley, M; Joyce, M; Reddy, V; Keane, S; Murphy, T; Mylotte, D; Hynes, B; Rosseel, L; Sharif, F; MacNeill, B; et al.
Abstract : Introduction: The National Clinical Programme for Acute Coronary Syndrome in Ireland has successfully improved outcomes for patients presenting with STEMI since its introduction in 2010. 1 Appropriate activation of the PPCI protocol is crucial to ensure timely reperfusion for patient with STEMI, while ensuring resources are not over-utilised for patients not requiring urgent PPCI. The aim of this review therefore was to establish the current rate of appropriate activation and false activation for the PPCI service in Galway. Methods: Phone records from the dedicated STEMI PPCI telephone number for the Galway PPCI centre were compared to simultaneously transmitted ECGs over a period from 01/01/2019 to 31/03/2019 inclusive (figure 1, table 1 ). A phone call record corresponding with a transmitted ECG for a new patient was considered activation of the PPCI protocol. These records were compared to the local STEMI database for patients transferred direct to the cardiology team for PPCI. All activations had the corresponding ECG assessed for STEMI criteria as per the ESC guidelines. Results: 171 activations of the STEMI PPCI service were recorded from 01/01/2019 to 31/03/2019 inclusive and 71 (42%) were accepted direct to Cardiology for management: 58 patients (34%) were correctly diagnosed with STEMI, 13 patients (7%) were transferred to the direct care of the cardiology team. Five patients (3%) underwent immediate angiography and had no coronary artery disease. Of the 100 patients not transferred directly to cardiology, 61 (36%) patients had ECGs which met ESC ECG criteria 2 for STEMI but did not have clinical symptoms consistent with STEMI: LBBB (n=30, 18%), RBBB (n=17, 10%), ST segment elevation (n=8, 5%), paced rhythms (n=6, 4%). 39 patients (23%) had neither ECGs consistent with STEMI nor symptoms requiring urgent transfer for PPCI: Non-specific changes or T-wave inversions (n=30, 18%), normal sinus rhythm (n=7, 5%) and Wellen's pattern (n=2, 1%). 67 of 100 false activations occurred during on-call hours. The national ambulance service activated the PPCI protocol for 127 cases, of which 39 (31%) cases were correctly diagnosed as STEMI. 52 (39%) patients had ECGs consistent with ESC ECG criteria [2] for STEMI without symptoms and 29 (23%) had neither ECG criteria nor symptoms. In total 44 activations were received from peripheral hospitals, 19 of which were correctly diagnosed as STEMI (43%). 9 (21%) patients had ECG changes consistent with ESC ECG criteria [2] for STEMI without symptoms, and 10 patients(23%) had neither ECG criteria nor symptoms. Conclusion: This review identifies important subgroups of patients who were referred for PPCI, in particular 23% of patients who did not require discussion, and 36% of patients who should have discussion with cardiology services before initiating transfer to the catheterisation laboratory.